Managing Workplace Conflicts in Nigerian Organisations: Insights for Strengthening National Security and Social Cohesion (Abuja Journal of Sociological Studies, 2026)
Workplace conflicts remain a persistent challenge in Nigerian organisations, often undermining productivity, employee well-being, and industrial harmony. Beyond organisational boundaries, unresolved conflicts escalate into labour unrest, social discontent, and threats to national security and social cohesion. This study explores how workplace conflicts are managed in Nigerian organisations and the implications for broader societal stability. The study adopted a qualitative research design, drawing primarily on secondary data sources, including peer-reviewed journal articles, government policy documents, industry reports, and publications from labour unions. A thematic content analysis was conducted to synthesis recurring patterns in the causes of conflict, the strategies deployed for resolution, and the outcomes for organisations and society. Findings show that economic hardship, wage disputes, poor leadership communication, and weak institutions are the main drivers of conflict. While negotiation and collective bargaining are the dominant management strategies, their effectiveness is undermined by mistrust and poor enforcement. Mismanaged conflicts lead to strikes, low productivity, and unrest, threatening cohesion, whereas inclusive conflict resolution strengthens organisational resilience and stability. The study concludes that effective workplace conflict management is both an organisational necessity and a national security strategy. It recommends institutionalised mediation, leadership training, participatory organisational cultures, and integration of workplace stability into Nigeria's security agenda